Low Birth Weight Associated with Maternal Age, Parity and Intergenesic Space: A Study in the Uvira Town in Democratic Republic of Congo - Kabanga, Alexandre Kabanga wa; Islam, Mohammad Shahidul (European Journal of Applied Sciences, 2024)
The Uvira health zone has never benefited from a study on low birth weight, while the neonatal mortality rate remains high. Low birth weight is an important public health indicator because of the strong association between birth weight and infant morbidity and mortality. This is a cross-sectional, retrospective study conducted over a ten-month period, from June 2021 to March 2022. In order to achieve a representative study of the city of Uvira, we identified 6 maternity hospitals willing to provide data from their facilities during the study, and spread over the 3 communes of the city of Uvira, with 2 most frequented maternity hospitals per commune. We selected births from the delivery registers of six health facilities in the city between June 2021 and March 2022 (n=802). We estimated the frequency of new borns with a birth weight of less than 2500 grs, explained the trends and also checked whether early maternal age, increased parity and small inter-genesic space deviation increased the risk of low birth weight. We describe for the first time data on low birth weight in the city of Uvira. A total of 21.1% of 802 births were associated with low birth weight. A strong correlation between low birth weight and maternal age (r=0.02, CI=95%, P-value=0.00000), parity (r=0.003, CI=95%, P-value=0.000001) and inter-genesic space (r=0.02, CI=95%, P-value=0.000809) was noted. It is important to conduct further studies to establish the cause-effect relationship for other determinants with a view to specific interventions to reduce perinatal morbidity and mortality.